Accession of Movables to lLand, South African Law and Dutch Law - Knobel, Ina (Comparative and International Law Journal of Southern Africa, 2022)
Accession is an original method of acquisition of ownership. For purposes of this article it refers to the situation where movable things which are attached to land permanently become part of the land and therefore the property of the owner of the land. This method of acquisition of ownership is called ‘building’ or ‘inaedificatio’ in South African law. The Dutch Civil Code provides that buildings or other improvements that have been united with land in a durable manner become immovable things through ‘vertical accession’. In this article, the criteria to determine whether a movable thing becomes permanently attached to land that are applied in South African law are referred to and are compared to those applicable in Dutch law. An interesting aspect in this field of study, which will specifically be addressed in this article, is the question whether objective or subjective criteria should be considered when determining whether a movable thing became an immovable thing through accession or not.